Complete mitogenome of endemic plum-headed parakeet Psittacula cyanocephala - characterization and phylogenetic analysis. - Prateek Dey; Sanjeev Kumar Sharma; Indrani Sarkar; Swapna Devi Ray; Padmanabhan Pramod; Venkata Hanumat Sastry Kochiganti; Goldin Quadros; Saurabh Singh Rathore; Vikram Singh; Ram Pratap Singh (PLoS ONE)
Psittacula cyanocephala is an endemic parakeet from the Indian sub-continent that is widespread in the illegal bird trade. Previous studies on Psittacula parakeets have highlighted taxonomic ambiguities, warranting studies to resolve the issues. Since the mitochondrial genome provides useful information concerning the species evolution and phylogenetics, we sequenced the complete mitogenome of P. cyanocephala using NGS, validated 38.86% of the mitogenome using Sanger Sequencing and compared it with other available whole mitogenomes of Psittacula. The complete mitogenome of the species was 16814 bp in length with 54.08% AT composition. P. cyanocephala mitogenome comprises of 13 protein-coding genes, 2 rRNAs and 22 tRNAs. P. cyanocephala mitogenome organization was consistent with other Psittacula mitogenomes. Comparative codon usage analysis indicated the role of natural selection on Psittacula mitogenomes. Strong purifying selection pressure was observed maximum on nad1 and nad4l genes. The mitochondrial control region of all Psittacula species displayed the ancestral avian CR gene order. Phylogenetic analyses revealed the Psittacula genus as paraphyletic nature, containing at least 4 groups of species within the same genus, suggesting its taxonomic reconsideration. Our results provide useful information for developing forensic tests to control the illegal trade of the species and scientific basis for phylogenetic revision of the genus Psittacula.